2016
DOI: 10.1039/c5ra20770c
|View full text |Cite
|
Sign up to set email alerts
|

Self-assembled nc-Si-QD/a-SiC thin films from planar ICP-CVD plasma without H2-dilution: a combination of wide optical gap, high conductivity and preferred 〈220〉 crystallographic orientation, uniquely appropriate for nc-Si solar cells

Abstract: Spontaneous miniaturization and rapid synthesis of self-assembled nc-Si-QDs of 〈220〉 orientation in high crystalline nc-Si-QD/a-SiC thin films of high conductivity and wide optical gap is obtained in ICP-CVD, from (SiH4 + CH4)-plasma, without H2-dilution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 56 publications
0
1
1
Order By: Relevance
“…3, which indicates that J sc increased to maximum (13.08 mA/cm 2 ) with E g = 1.91 eV and then dropped to 12.47 mA/cm 2 with E g increased further. This seems different from the simulation result of J sc versus optical gap of the a-SiC:H p-layers [10] . However, we noted that Hou et al [23] and Liu et al [24] also reported similar dependence of J sc on E g (the 1st to 3rd column of Table 2).…”
Section: Resultscontrasting
confidence: 96%
See 1 more Smart Citation
“…3, which indicates that J sc increased to maximum (13.08 mA/cm 2 ) with E g = 1.91 eV and then dropped to 12.47 mA/cm 2 with E g increased further. This seems different from the simulation result of J sc versus optical gap of the a-SiC:H p-layers [10] . However, we noted that Hou et al [23] and Liu et al [24] also reported similar dependence of J sc on E g (the 1st to 3rd column of Table 2).…”
Section: Resultscontrasting
confidence: 96%
“…The E g of "window" p-layer could be increased by alloying with additional elements such as C and O. The alloys such as amorphous hydrogenated silicon carbide (a-SiC:H) [7,8] and amorphous silicon oxide (a-SiO:H) [9] provided wide E g and enabled high V oc above 1 V. However, the electrical conductivity of the a-SiC:H or a-SiO:H p-layer would become poorer if the gaps were opened further [10,11] . Nanocrystalline or protocrystalline film could be a better alternative due to its wide gap and high electrical conductivity.…”
Section: Introductionmentioning
confidence: 99%